Institusi Keluarga Perspektif Feminisme - A. Abdulloh Khuseini (TSAQAFAH, 2017)
Feminism does not only aim to insist on getting the equal rights between men and women, but to break the patriarchal system that is considered as a discrimination. This claim then sparks criticism toward a family institution that shackles women’s freedom. Feminists view the family institution as the frst “enemy” to be eliminated or diminished in its role. Family is considered as the source of all existing social imbalances, especially from the rights and duties between husband and wife. Family institutions place women in a weak position. This article aims to explain the concept and history of family institution in the thought of feminists. And then, it will uncover the social impact of their thought or concept. As a comparison and answer, this article also explains how the family institution in the view Islamic worldview. From article concludes that feminists that inﬂuenced by Western worldview have destroyed the pillars of family. The concept they thought has given disharmony in the family. They think that family is not something necessary and important. This can be seen from the facts that exist, for example wives who are no longer willing to do homework, such as cleaning the house, cooking, or caring for their children. In contrast, Islam teaches justice between husband and wife in the family institution. No one is superior to another. When Islam asks husband to fulfll duties over wife, wife is also required to fulfll obligations to her husband. From here, harmony within the family institution will be established.